Prevalence of Shiga-toxigenic Escherichia coli in Mauritian dairy cattle - Sébatien Ian Lloyd Thierry; Sunita Jeewantee Santchurn; Yasmina Jaufeerally-Fakim; James E. Gannon (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2015)
Shiga-toxigenic Escherichia coli (STEC) are important human pathogens (1). They are characterized by their ability to produce Shiga toxins (stx1 and stx2). Seven STEC have been shown to withstand food processing procedures that are expected to ensure food safety. Clinical symptoms associated with STEC infection can vary from abdominal cramps and acute bloody diarrhea to more severe aftereffects including hemorrhagic colitis, hemolytic uremic syndrome and thrombocytopenic purpura, which can lead to kidney failure and death.